Employees’ Perception of Corporate Sustainable Development: A Bibliometric Examination - Erika-Ligia Heler (Ovidius University Annals: Economic Sciences Series, 2024)
This research endeavor explores employees’ perception of corporate sustainable development across its three fundamental dimensions – economic, social and environmental. To assess the primary research directions linked to the subject, a quantitative bibliometric analysis of the literature was conducted by selecting the key aspects of the topic within a significant body of publications indexed in the Web of Science database, consisting of a total of 1.031 scientific documents. Subsequent data analysis was carried out using the bibliometric networking software VOSviewer version 1.6.19. This was accomplished through the mapping of keyword co-occurrence, co-citation of referenced papers, as well as collaborative authorship, revealing the prominent areas of investigation associated with the topic under examination.